Analysis of the Issuance of Land Use Rights in the Name of the Medan City Government from a Fiqh Siyasah Perspective (Study of Decision Number 296/G/2019/PTUN.Medan) - Parinduri, Muhammad Rafli; Permata, Cahaya (IHSA Institute, 2025)
This study aims to analyze the issuance of land use rights by the Medan City Government from the perspective of Fiqh Siyasah, focusing on Decision Number 296/G/2019/PTUN.Medan. The problem in this case began with the issuance of Certificate of Use Rights Number 01653/Kesawan Village dated March 14, 2018 with a measurement letter Number 00194/Kesawan/2018 covering an area of 1,752 m² in the name of the Medan City Government. The issuance of the certificate was then challenged to the Medan PTUN by the Plaintiff who is the heir of Dalip Singh Bath, who claims to be the legal owner of the land and buildings that are the object of the case. The Plaintiff feels legally and administratively disadvantaged by this action because the issuance of the right of use was carried out without involving or paying attention to existing inheritance rights. This research is a normative legal research with a statute, conceptual, and judicial case study approach. Data were collected through literature studies and analyzed qualitatively. The research results show that the issuance of land use rights by the Medan City Government has led to ownership conflicts with heirs. From a Fiqh Siyasah perspective, government actions should prioritize justice, public interest, deliberation, and the protection of property rights. This study emphasizes the importance of synchronizing positive law with sharia principles in land management by local governments